The Prognosis and Oncological Predictor of Urachal Carcinoma of the Bladder: A Large Scale Multicenter Cohort Study Analyzed 203 Patients With Long Term Follow-Up - Yu, Young Dong; Ko, Young Hwii; Kim, Jong Wook; Jung, Seung Il; Kang, Seok Ho; Park, Jinsung; Seo, Ho Kyung; Kim, Hyung Joon; Jeong, Byong Chang; Kim, Tae-Hwan; Choi, Se Young; Nam, Jong Kil; et al. (Frontiers in Oncology, 2021)
Aim This study evaluated the prognosis and survival predictors for bladder urachal carcinoma (UC), based on large scale multicenter cohort with long term follow-up database. Methods A total 203 patients with bladder UC treated at 19 hospitals were enrolled. Clinical parameters on carcinoma presentation, diagnosis, and therapeutic methods were reviewed for the primary cancer and for all subsequent recurrences. The stage of UC was stratified by Mayo and Sheldon pathological staging system. Oncological outcomes and the possible clinicopathological parameters associated with survival outcomes were investigated. Results The mean age of the patients was 54.2 years. Among the total of 203 patients, stages I, II, III, and IV (Mayo stage) were 48 (23.8%), 108 (53.5%), 23 (11.4%), and 23 (11.4%), respectively. Gross hematuria and bladder irritation symptoms were the two most common initial symptoms. The mean follow-up period was 65 months, and 5-year overall survival rates (OS), cancer-specific survival rates (CSS), and recurrence-free survival rates (RFS) were 88.3, 83.1, and 63.9%, respectively. For the patients with Mayo stage ≥III, OS, CSS, and RFS were significantly decreased to 38.0, 35.2, and 28.4%, respectively. The higher pathological stage (Mayo stage ≥III, Sheldon stage ≥IIIc), positive surgical margin (PSM), and positive lymphovascular invasion (PLM) were independent predictors of shorter OS, CSS, and RFS. Conclusion The pathological stage, PSM, and PLM were significantly associated with the survival of UC patients, emphasizing an importance of the complete surgical resection of tumor lesion.